Hubungan Jarak Kehamilan dan Kepatuhan Mengkonsusi Tablet Fe dengan Kejadian Anemia pada Ibu Hamil di Wilayah Kerja Puskesmas Rambah Samo 1. - Ratih Nur Sri Sutrianingsih., Heny Sepduwiana, (Jurnal Martenity and Neonatal, 2017)
Understanding Anemia in pregnancy is defined as a decrease in hemoglobin levels of less than 11 g / dl during pregnancy in the first and third trimesters less than 10 g / dl during post partum and second semester. The increase in blood in pregnancy has begun since 10 weeks of pregnancy and peaked in pregnancy between 32 and 36 weeks. The prevalence of ibuprict anemia in Indonesia is 70% or 7 out of 10 pregnant women suffering from anemia.Anemia of iron deficiency is encountered in 40% of pregnant women.The purpose of this study was to determine the relationship of pregnancy distance and compliance of Fe tablets with the incidence of anemia in pregnant women. The research method is quantitative analytic with cross sectional design. Sampling method was done by random sampling with total sample 66 people. Data collection is done using primary data. Analysis of research data is univariate analysis and bivariate analysis with chi square test. The result of the research on the degree of confidence (OR 95% CI) was obtained no relationship of gestational distance with the incidence of anemia with P value = 0.414 and there was a compliance relationship consuming fe tablet with the incidence of anemia with value P = 0.001. conclusions from this study showed no significant relationship between gestational distance with the incidence of anemia and there was a compliance relationship consuming fe tablet with the incidence of anemia. Suggestions for pregnant women are encouraged to consume fe tablets during pregnancy and for the workforce, especially the village midwife, giving more counseling and counseling about overcoming anemia in pregnancy. So it can increase the knowledge of the community, especially pregnant women.